2013
DOI: 10.1152/jn.00004.2013
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic connections in the anterior part of the bed nucleus of the stria terminalis

Abstract: Turesson HK, Rodríguez-Sierra OE, Pare D. Intrinsic connections in the anterior part of the bed nucleus of the stria terminalis. J Neurophysiol 109: 2438 -2450, 2013. First published February 27, 2013 doi:10.1152/jn.00004.2013.-Intrinsic connections in the anterior portion of the bed nucleus of the stria terminalis (BNST-A) were studied using patch recordings and ultraviolet (UV) glutamate uncaging (GU) in vitro. UV light was delivered at small BNST-A sites in a grid-like pattern while evoked responses were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 61 publications
(22 reference statements)
4
23
1
Order By: Relevance
“…We will perform further rigorous experiments to examine this and correlate input strength and pattern to cell morphology. Our findings appear to be consistent with a recent study (Turesson et al 2013) that examined the intrinsic connections of rat BNST using glutamate uncaging in a relatively coarse manner. They reported that glutamate uncaging via UV LED light (150 m in diameter and 50 ms in duration) elicited GABAergic inhibitory postsynaptic potentials more frequently than excitatory postsynaptic potentials (Turesson et al 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We will perform further rigorous experiments to examine this and correlate input strength and pattern to cell morphology. Our findings appear to be consistent with a recent study (Turesson et al 2013) that examined the intrinsic connections of rat BNST using glutamate uncaging in a relatively coarse manner. They reported that glutamate uncaging via UV LED light (150 m in diameter and 50 ms in duration) elicited GABAergic inhibitory postsynaptic potentials more frequently than excitatory postsynaptic potentials (Turesson et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings appear to be consistent with a recent study (Turesson et al 2013) that examined the intrinsic connections of rat BNST using glutamate uncaging in a relatively coarse manner. They reported that glutamate uncaging via UV LED light (150 m in diameter and 50 ms in duration) elicited GABAergic inhibitory postsynaptic potentials more frequently than excitatory postsynaptic potentials (Turesson et al 2013). These and further studies will provide important information for understanding the general principles of BNST local circuit organization.…”
Section: Discussionsupporting
confidence: 92%
“…Also, given the prevalence of LTB cells in the three regions, it will be important to determine in what behavioral states these neurons fire tonically vs. in bursts. Given that BNST-AL sends strong GABAergic projections to BNST-AM and AV (Turesson et al 2013), it is likely that these inhibitory inputs play a critical role in setting the firing mode of LTB cells in the other two regions.…”
Section: Morphological Correlates Of Electroresponsive Propertiesmentioning
confidence: 99%
“…The anterior BNST is comprised of three major anatomical subdivisions: the anterodorsal (adBNST), anterolateral (alBNST), and anteroventral (avBNST; Dong et al, 2001b;Ju & Swanson, 1989;Turesson, RodriguezSierra, & Pare, 2013). There are many intrinsic connections between each subdivision, the nature of which appears to be largely dependent on subdivision (Dong & Swanson, 2004a, 2004bDong et al, 2001b;Turesson et al, 2013).…”
Section: The Anterior Bnst: Microstructure Microcircuitry and Chemomentioning
confidence: 99%
“…There are many intrinsic connections between each subdivision, the nature of which appears to be largely dependent on subdivision (Dong & Swanson, 2004a, 2004bDong et al, 2001b;Turesson et al, 2013). For example, intra BNST projections from the alBNST are primarily inhibitory, whereas intraBNST projections from the avBNST and the adBNST are inhibitory and excitatory.…”
Section: The Anterior Bnst: Microstructure Microcircuitry and Chemomentioning
confidence: 99%